2020
DOI: 10.5664/jcsm.8618
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting CPAP device respiratory indices in children

Abstract: Study Objectives: An increasing number of children with obstructive sleep apnea (OSA) require treatment with continuous positive airway pressure (CPAP). This study aimed to determine whether automatic respiratory indices from a CPAP device accurately predict manually determined respiratory indices derived from overnight polysomnography (PSG) in children. Methods: Consecutive children undergoing manual CPAP titration PSG using a ResMed VPAP ST-A (S9) were included. The apnea-hypopnea index (AHI), apnea index (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Currently, there are limited data comparing the measurement of AHI by the gold-standard PSG and home-NIV machine downloadable data. Mihai et al, 48 those with severe OSA showed a reduced number of days used. 30,50 Upper airway surgery is often the first-line treatment of OSA in children with DS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, there are limited data comparing the measurement of AHI by the gold-standard PSG and home-NIV machine downloadable data. Mihai et al, 48 those with severe OSA showed a reduced number of days used. 30,50 Upper airway surgery is often the first-line treatment of OSA in children with DS.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, there are limited data comparing the measurement of AHI by the gold‐standard PSG and home‐NIV machine downloadable data. Mihai et al, 48 concluded that the ResMed S9 home CPAP device significantly underestimated residual OSA and may not be diagnostic in terms of respiratory indices; however, a diminishing AHI is reassuring in the context of a stable patient. Khirani et al, 49 also compared built‐in software automatic scoring in‐home CPAP machines to PSG manual measures of AHI.…”
Section: Discussionmentioning
confidence: 99%
“…However these studies were of obese children without co‐morbidities 16 or with small numbers of comorbidities (17%) 15 and poor CPAP adherence (average CPAP use was only 2.8 h/night) 15 or adherence was not reported at followup 16 . Previous studies from our group in Australia reflect a different population, 3,17,18 with higher co‐morbid syndromes (65−73%) and higher average hours of use (4.7−6.3 h/night). Furthermore, these previous studies used a general measure of QOL in children (the PedsQL 15,16 ) which may miss domains of QOL particularly relevant to children with intellectual disability 19 and does not address sleep symptoms.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies have shown that the breathing pattern data may not be accurate, 39 and the residual respiratory events overestimated. [40][41][42] The built-in software data should therefore always be considered with caution. A recent bench study, hypothesizing that patient's breathing detection is based on a minimal tidal volume, reported that some level I and II CPAP devices may be suitable for younger children, however, these findings have not been clinically validated.…”
Section: Cpap Devicesmentioning
confidence: 99%